2020
DOI: 10.1088/1757-899x/814/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Fracture analysis of center cracked laminated composite plate subjected to bi-axial loading using extended finite element method

Abstract: Among various numerical method, finite element method (FEM) is extensively used but handling the fracture problem with conventional FEM is time-consuming and costly. So, extended finite element method (XFEM) which is based on partition of unity method and enrichment functions is used to handle material with discontinuities. In the present study, fracture analysis of center cracked layered composite plate under different biaxial loadings (tensile, shear and combined) using XFEM is investigated and mixed mode st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Finite element method based on partition of unity method and enrichment function was used 28 to predict the fracture properties of composite laminates with central crack under bi-axial loading at different failure modes. The results gave reported that fiber orientation significantly affected the plane of fracture, moreover the crack orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Finite element method based on partition of unity method and enrichment function was used 28 to predict the fracture properties of composite laminates with central crack under bi-axial loading at different failure modes. The results gave reported that fiber orientation significantly affected the plane of fracture, moreover the crack orientation.…”
Section: Introductionmentioning
confidence: 99%